Land Reform in the Republic of South Africa: Social Justice or Populism? - Żukowski, Arkadiusz (Werkwinkel, 2017)
In the paper land reform in South African political discourse will be investigated, especially the process of its politicization. How the topic of land reform is used by political forces, especially the ruling party; the African National Congress and current President Jacob Zuma. Does the Republic of South Africa take a populist turn on land reform or is it some kind of social justice after the suppression of the apartheid era and decades before? The political disputes and decisions will be analysed in confrontations with the fundamentals and values of a democratic state as a guarantee of property rights, private ownership and free market principles (dilemma of the problem of willing buyer - willing seller). It will be necessary to present the historical background of land problem in the RSA. The problem will be investigated in connection with the socio-economic situation of the RSA. The study will also tackle the problem of social and economic inequality from the perspective of politics. In the paper, a mix of primary and secondary research methods of data collection and analysing will be used. Theoretical framework will be based on assumptions of political discourse and the paradigm of “classic” land reform.